Optimization of parameters for skin cancer diagnostics using reflected terahertz radiation - Milosevic, M.; Stevanovic, N.; Markovic, V. M. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
In this paper, the reflected THz radiation from the healthy skin and skin affected by cancer was analyzed. For that purpose, finite difference time domain (FDTD) method for electromagnetic wave propagation was adjusted and applied to simulate THz radiation propagation according to the human skin. Here, radiation from 0.1 to 1 THz was considered. Multi-layer skin model was applied with given electric parameters for each skin layer. The parameters used were conductivity and dielectric constant. The values of parameters depend on frequency and highly depend on whether the skin is healthy or not. It was found that the intensity of reflected radiation from the cancerous skin is greater than the intensity of reflected radiation from the healthy skin, and that the difference between these two intensities increases with increasing frequency. It was also obtained that the distribution of reflected radiation is similar to the distribution of incident radiation, while absorption of transmitted radiation is very small. These results obtained within this paper are significant because they indicate that the reflected radiation from the skin could be used for skin cancer diagnostics.
Optica Applicata, Vol. 55, 2025, nr 2, s. 181-195
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; skin; terahertz radiation; cancer; FDTD method